Immunotherapy in lung cancer - Awad, Mark M. (Henry Stewart Talks, 2019)
Changing treatment paradigm for stage IV non-small cell lung cancer, Immunotherapy after chemoradiation in unresectable stage III lung cancer, Investigating immune checkpoint inhibition in early-stage surgically-resectable lung cancer, Immunotherapy for small cell lung cancer, Biomarkers of response to immunotherapy in lung cancer